3D Research Challenges in Cultural Heritage III: Complexity and Quality in Digitisation - (:unkn) unknown (My University, 2023)
This open access book presents a collection of papers focusing on current 3D research challenges in the domain of digital cultural heritage. 3D technologies find considerable use within the field of cultural heritage at the beginning of the 21st century, for example in the areas of data acquisition, modeling, archiving in local repositories, harvesting in digital libraries and their long-term preservation. This volume put emphasis on a number of challenges facing 3D research in the 2D/3D digitization of tangible objects and their transformation to digital/virtual/memory twins; the interplay of geometry, semantics and the recovery and management of knowledge in digital cultural heritage; the handling of 3D data via the Cloud on the Internet and mobile devices; the presentation of cultural heritage content in 3D to the general public; and the 3D reproduction of cultural heritage objects from virtual to real.
Keywords: 3D Digitization; Digital Cultural Heritage; IIIF 3D; Digital Documentation; 3D Quality Model; 2D/3D Interoperability; Extended Reality; Virtual Reality; Photogrammetry; Digital Twin; 3D Data